Boundary condition and fuel composition effects on injection processes of high-pressure sprays at the microscopic level. (July 2016) - Manin, J.; Bardi, M.; Pickett, L.M.; Payri, R.
Highlights: Actual rate of injection ramp-up clearly affects initial spray penetration. Spray development and dispersion are linked to injector needle position. Sprays of ethanol are wider than those of n-dodecane due to in-nozzle cavitation. End of injection velocity measurements indicate that complete mixing assumption is reasonable in the near-nozzle region. Abstract: Detailed imaging of n-dodecane and ethanol sprays injected in a constant-flow, high-pressure, high-temperature optically accessible chamber was performed. High-speed, diffused back-illuminated long-distance microscopy was used to resolve the spray structure in the near-nozzle field. The effect of injection and ambient pressures, as well as fuel temperature and composition have been studied through measurements of the spray penetration rates, hydraulic delays and spreading angles. Additional information such as transient flow velocities have been extracted from the measurements and compared to a control-volume spray model. The analysis demonstrated the influence of outlet flow on spray development with lower penetration velocities and wider spreading angles during the transients (start and end of injection) than during the quasi-steady period of the injection. The effect of fuel composition on penetration was limited, while spreading angle measurements showed wider sprays for ethanol. In contrast, varying fuel temperature led to varying penetration velocities, while spreading angle remained constant during the quasi-steady period of the injection. Fuel temperature affected injector performance, with shorter delays as fuel temperature was increased. The comparisons between predicted and measured penetration rates showed differences suggesting that the transient behavior of the spreading angle of the sprays modified spray development significantly in the near-field. The reasonable agreement between predicted and measured flow velocity at and after the end of injection suggested that the complete mixing assumptions made by the model were valid in the near nozzle region during this period, when injected flow velocities are reduced.